Overexpression of SOX9 alleviates the progression of human osteoarthritis in vitro and in vivo - Ouyang Y; Wang W; Tu B; Zhu Y; Fan C; Li Y (Dove Medical Press, 2019)
Yuanming Ouyang,1,2 Wei Wang,1,2 Bing Tu,1,2 Yi Zhu,1,2 Cunyi Fan,1,2 Yanfeng Li1,21Department of Orthopedics, Shanghai Sixth People’s Hospital East Campus Shanghai University of Medicine and Health, Shanghai 201306, People’s Republic of China; 2Department of Orthopedics, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai 200233, People’s Republic of ChinaPurpose: Recent findings have identified that SOX9 served as a key role during the pathogenesis of osteoarthritis (OA). This study aimed to investigate the mechanisms by which SOX9 regulated the formation of OA in vitro and in vivo.Materials and methods: The relative expressions of SOX9 in patients with OA and normal fracture of thighbone were analyzed by real-time-PCR. In vitro, IL-1β induced inflammatory response in human chondrocytes was used to evaluate the function of SOX9. The recombinant SOX9 lentivirus vector (Lenti-SOX9) was used to upregulate the expression of SOX9 in cells. ELISA was used to measure the concentration of tumornecrosis factor-α (TNF-α). The protein expressions of SOX9, matrixmetalloproteinase-13 (MMP13), Collagen II, Aggrecan and Smad3 were analyzed by Western blot. Cell proliferation and cell apoptosis were detected by CCK-8 assay and flow cytometry, respectively. In vivo, the effect of SOX9 on surgically induced OA mice was evaluated.Results: The gene level of SOX9 was remarkably downregulated in patients with OA compared with normal people, while the concentration of TNF-α was upregulated. In addition, IL-1β reduced the expressions of SOX9, Collagen II and Aggrecan and increased the level of MMP13 in chondrocytes. Moreover, Lenti-SOX9 notably inhibited IL-1β-induced growth inhibition and apoptosis in chondrocytes via increasing the expression of Smad3. Finally, Lenti-SOX9 markedly alleviated the symptoms of OA mice in vivo.Conclusion: Upregulation of SOX9 inhibited IL-1β-induced inflammatory response via increasing the level Smad3 in human chondrocytes and exhibited therapeutic effect on surgically induced OA mice in vivo. Therefore, SOX9 may serve as a potential target in the treatment of OA in the future.Keywords: SOX9, osteoarthritis, collagen, inflammation, IL-1β